Tales of High Priests and Taxes : The Books of the Maccabees and the Judean Rebellion against Antiochos IV - Honigman, Sylvie, 1965- (Book collections on Project MUSE., 2014)
In the wake of the conquests of Alexander the Great, the ancient world of the Bible-the ancient Near East-came under Greek rule, and in the land of Israel, time-old traditions and Greek culture met. But with the accession of King Antiochos IV, the soft power of culture was replaced with armed conflict, and soon the Jews rebelled against their imperial masters, as recorded in the Biblical books of the Maccabees. Whereas most scholars have dismissed the biblical accounts of religious persecution and cultural clash, Sylvie Honigman combines subtle literary analysis with deep historical insight.